(untitled) (Journal of the College of Basic Education, 2024)
The Current research aims identify the impact of the Wallace model on Systemic thinking among Firest-Grade Intermediate Students. TO achieve this objective,the following null hypothesis was formulated: There is no statistically significant difference at the (0.05) level between the average scores of students in the experimental group who studied according to the Wallace model and average scores of students in the control group who studied using the conventional method in systemic thinking . The research community consists of firest-gride intermediate students in government secondary and intermediate schools for girls in Baghdad Educational Directorate for the academic year (2023-2024) , Intermediate Al-Qabas for girls was selected intentional from the schools of the current research community, The two sections (A) and (B) were chosen randomly to represent section )A) , The experimental group consisting of (36) students who studied according to the Wallace model , and section (B) consisting of (37) students who studied using the the conventional method. The experimental design whith two groups (experimental and control) was adopted, whith one partially controlling the other in some of the post-test variables systemic thinking. The experimental was implemented in the firest semester of the academic year (2023-2024) , The research groups ( experimental and control ) were rewarded for several variables , including students ( chronological age in months , pre-knowledge test , Raven’s intelligence test and prior systemic thinking scale) . To achieve the researcher objective , The researcher adopion scale for (Dolansky and More:2011) , The discriminatory power of each item of the scale in addition to extracting construct validity represented by (the relationship of the item score to the total score) the results indicated the superiority of the female students of the experimental group who studied according to the Wallace model over the female students of the control group who studied according to the usual method of systemic thinking, with a significant effect size.